Early Identification of Handicapped Children. Computer Assisted Remedial Education Report No. R-36 - Cartwright, G. Phillip; Cartwright, Carol A.; Pennsylvania State Univ., University Park. Computer-Assisted Instruction Lab. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1972)
The handbook is intended to be part of a graduate course entitled "Introduction to Exceptional Children" which is taught via computer assisted instruction and emphasizes the social, psychological, and physiological characteristics of the mentally, visually, aurally, physically, emotionally, or neurologically handicapped primary grade child to whom, if identified early, remedial treatment can be given before educational retardation becomes a problem. The following topics are treated: educational information processing model; interrelationships of handicaps; decision process; gathering information about children; reliability, validity, and usability of evaluation procedures; individual differences and normality; profiles of individual differences; Denver Developmental Screening Test; mental retardation; the disadvantaged; emotional disturbance; First Grade Screening Test; Visual problems; hearing problems; speech problems; Metropolitan readiness tests; motor, physical, and health problems; drug abuse; learning disabilities; documentation and referral procedures; and case histories. A glossary of approximately 350 terms gives definitions of terms such as ability profile, perseveration, and sociogram as they are used in the course. Stressed throughout the course are the decision process, the information processing model, observable behaviors, individualization of instruction, and data gathering and documentation. (See ED 054 063 for a related document). (DB)
Microfiche.
Keywords: Behavior; Computer Assisted Instruction; Decision Making; Exceptional Child Education; Glossaries; Graduate Study; Guidelines; Handicapped Children; Identification; Individualized Instruction; Inservice Teacher Education; Testing